Association Between Basal Metabolic Rate and All-Cause Mortality in a Prospective Cohort of Southern Chinese Adults - Han, Fengyu; Hu, Feng; Wang, Tao; Zhou, Wei; Zhu, Linjuan; Huang, Xiao; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Physiology, 2022)
Objectives: To assess the relationship between basal metabolic rate (BMR) and all-cause mortality in southern Chinese adults. Methods: We prospectively examined the relationship between BMR and all-cause mortality in 12, 608 Southern Chinese adults with age ≥ 35 years who participated in the National Key R&D Program from 2013-2014 to 2019-2020. Cox proportional hazards models were used to examine the association between BMR and all-cause mortality. Results: 809 deaths (including 478 men and 331 women) occurred during a median follow-up period of 5.60 years. All-cause mortality was higher in elderly individuals than in nonelderly individuals (11.48% vs. 2.04%, P < 0.001) and was higher in male subjects than in female subjects (9.84% vs. 4.56%, P < 0.001). There was a significantly inverse relationship between BMR levels and all-cause mortality in elderly male individuals (adjusted-HR per SD increase: 0.80, 95% CI 0.70 to 0.91, P < 0.001). Compared to BMR levels ≤ 1115 kJ/day, there was lower all-cause mortality in third and highest BMR quartiles in the elderly male subjects (adjusted-HR: 0.71, 95% CI 0.53 to 0.95, P = 0.022; adjusted-HR: 0.60, 95% CI 0.43 to 0.84, P = 0.003, respectively). Conclusion: An elevated BMR was independently inversely associated with all-cause mortality in elderly male subjects in a southern Chinese population.